M-learning as a means of supporting learners: Tomorrow’s technologies are already here, how can we most effectively use them in the e-learning age? - Stone, Andy; Alsop, Graham; Briggs, Jonathan; Tompsett, Chris (Proceedings of the International Conference on Networked Learning, 2002)
Mobile telephone ownership and usage is now almost ubiquitous amongst student communities, but until now has been largely passed over as a technology for supporting student learning. As increasingly powerful networks and handsets are developed, it is claimed that "m-learning" (mobile learning) will be one of the largest applications - but the potential of what can already be achieved has hardly been explored. This paper first explores the notions of complementary media and complexity. A survey of work undertaken globally illustrates how others have already attempted to apply Short Message Service (SMS) and Wireless Application Protocol (WAP) technologies in libraries and teaching. We summarise results of research recently completed at Kingston, adopting a learner-centred approach to forthcoming research and trials using current and future technologies.